'If someone donates 1000, they support you. If they donate 100 000, they have bought you'. Mixed methods study of tobacco, alcohol and gambling industry donations to Australian political parties. (25th November 2018) - Kypri, Kypros; McCambridge, Jim; Robertson, Narelle; Martino, Florentine; Daube, Mike; Adams, Peter; Miller, Peter
Abstract: Background and Aims: Business corporations' use of political donations to garner political influence is especially troubling in relation to products that damage human health. We sought to investigate patterns of donations to Australian political parties from tobacco, alcohol and gambling industry actors and the experiences of key informants. Design and Methods: We analysed public data on federal and state donations for 10 years to June 2015. We conducted 28 semi‐structured interviews with current and former politicians, ex‐political staffers and other key informants, concerning the role played by political donations of tobacco, alcohol and gambling companies in Australian politics. We examined temporal associations in donations data, and thematically analysed interviews. Results: Australian political parties declared donations of A14 million (US11 M) from tobacco (1.9 M), alcohol (7.7 M), gambling (2.9 M) and supermarket (1.7 M) entities, excluding donations below the 12 800 reporting threshold. Donations to the governing party increased substantially during debates about an alcohol tax and gambling law reform. Alcohol industry donations to major parties spiked ahead of elections. Interviewees identified the function of donations in terms of: (i) buying immediate influence; (ii) building long‐term relationships; (iii) exploiting a flawed political system; and (iv) the need to look beyond donations, for example, to favour exchange; and the public's right to know about corporate influence on policy‐makers. Discussion and Conclusions: The alcohol and gambling industries make substantial donations to influence particular decisions in the short term and build relationships over the long term. Banning corporate donations and publicly funding political parties warrant consideration to safeguard the integrity of public policy‐making.